Prevention of Risk of Falls and Musculoskeletal Disorders in Older People through Ergonomic exercise and Posture Screening - Hasyar, Andi Rizky Arbaim; Putri, Melda; Ahsaniyah, Andi Besse; Pudjiningrum, Andi Rahmaniar Suciani; Mustari, Yery; Hamisah, Hamisah; Rini, Ita; Hasbiah, Nurhikmawaty (Sarana Ilmu Indonesia (salnesia), 2025)
Aging is a natural process in the human life cycle. The increase in life expectancy has a positive impact on quality of life, but it also brings various consequences, one of which is the decline in physical and cognitive functions. As they age, the elderly become more susceptible to musculoskeletal disorders, which in turn increase the risk of falling. This community service activity aimed to enhance the understanding and awareness of the elderly regarding the importance of preventing falls and musculoskeletal disorders through ergonomic education and posture screening. The activity, themed